A proposito dell’infinito articolato nel Nuovo Testamento - Pierri, Rosario 1960- (2009)
This article summarizes and discusses some of the fundamental aspects of the theory proposed by D. Burk on the use of articular infinitives, found in his monograph dedicated to this subject. One of the results of this present research is that the linguistic approach used by Burk while on the one hand, provides a comprehensive analyisis of the syntax of the use of the articular infinitive, on the other, does not propose a clear theory for a better understanding of articular infinitives in the New Testament as an alternative to the traditional grammar theory.